Il genere grammaticale in tedesco, italiano e inglese: una microtipologia contrastiva - Gaeta, Livio (Linguistik Online, 2024)
The general tendencies regarding the gender of nouns are dealt with in the paper with the specific aim of building a contrastive microtypology of German, Italian and English. In particular, up to six different types and functions of gender will be distinguished and will be tested against the background of empirical data drawn from the three languages. Interesting phenomena of convergence and divergence at all levels of the respective linguistic systems pop out from the contrastive analysis, starting from the phonological level up to the pragmatic and cognitive dimension.